A Conceptual Model for Cybersecurity Governance. Issue 4 (2nd October 2021) - Yusif, Salifu; Hafeez-Baig, Abdul
Abstract: Cybersecurity is a growing problem associated with everything an individual or an organization does that is facilitated by the Internet. It is a multi-facetted program that can be addressed by cybersecurity governance. However, research has shown that many organizations face at least five basic challenges of cybersecurity. In this study, we developed a model for an effective cybersecurity governance that hopes to address these challenges, conceptualized as factors that must continuously be measured and evaluated. They are: (1) Cybersecurity strategy; (2) Standardized processes, (3) Compliance, (4) Senior leadership oversight, and (5) Resources.